Investigating the Market Failure Evidence The Case of Fuel Additive Next Generation Petrol and Diesel in India - R. Pazhanisamy; Thomas Mathew (ZBW – Leibniz Information Centre for Economics, 2024)
With the evolving landscape of automotive technologies and increased environmental regulations, there is a pressing need for advanced fuel additives that can enhance the performance, efficiency, and environmental footprint of next-generation combustion engines. The developed additive comprises a unique blend of detergents, cetane and octane boosters, antioxidants, and corrosion inhibitors, tailored to improve fuel efficiency, engine life, and emissions quality. The formulation also includes novel bio-based components that enhance the biodegradability and reduce the carbon footprint of the fuel, aligning with global sustainability goals. The introduction of this fuel additive not only promises to extend the operational life of next-generation engines but also supports the automotive industry's move towards more sustainable and environmentally friendly solutions. Future research will focus on optimizing the additive formulation for use with alternative fuels and exploring the potential impacts on emerging propulsion technologies. In this context a new generation fuel has introduced in India named super petrol which can add the values to the petrol by increasing vehicles performance and reducing the carbon emission with some minimal additional cost. But the market for such inevitable eco friendly product becomes disappeared in both the auto mobile industry and from the literature which demand and attempt to make an investigation into the market failure. This paper is attempted to fill this gap in the research.
Keywords: Q51; Q58; L71; O32; Q42; 330; Environmental effects of fuel; Environmental economics & government policy; Refining Hydrocarbon fuels; Management of Technological Innovation and R&; Alternative Energy Sources; Government policy and externalities